2023
DOI: 10.36740/merkur202302109
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events and Mental Diseases: The Role of Certain Neurotransmitters, Metalloenzymes and Hormones. Systematic Literature Review

Ivan R. Romash,
Iryna B. Romash,
Kateryna V. Dzivak
et al.

Abstract: Aim: To study the role of certain neurotransmitters (brain-derived neurotrophic factor (BDNF), 5-hydroxytryptamine (5-HT)), metalloenzymes (matrix met¬alloproteinase-9) (MMP-9) and hormones (ghrelin) in the pathogenesis of mental disorders associated with stress under the impact of traumatic events. Materials and methods: We conducted a systematic search of major electronic medical databases published before October 1, 2022. Such keywords as (post-traumatic stress disorder OR PTSD), (Brain-derived neurotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Regarding trauma exposure, numerous studies, including systematic reviews and metaanalyses, confirmed its negative effect on mental health (Romash et al, 2023). In particular, trauma affects well-being and results in a larger number of diseases throughout life, risky behavior and early death (Abraham and Walker-Harding, 2022), significant changes in selfperception (Barros et al, 2022) and social identity (Muldoon et al, 2019), an increase in the risk of depression, anxiety and low self-esteem (Downey and Crummy, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding trauma exposure, numerous studies, including systematic reviews and metaanalyses, confirmed its negative effect on mental health (Romash et al, 2023). In particular, trauma affects well-being and results in a larger number of diseases throughout life, risky behavior and early death (Abraham and Walker-Harding, 2022), significant changes in selfperception (Barros et al, 2022) and social identity (Muldoon et al, 2019), an increase in the risk of depression, anxiety and low self-esteem (Downey and Crummy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding trauma exposure, numerous studies, including systematic reviews and meta-analyses, confirmed its negative effect on mental health (Romash et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%